The effects of entrepreneurial marketing among small and medium enterprises (SMEs) in Bangladesh: its linkages towards competitive advantage and firm performance - Abu Shams Mohammad Mahmudul Hoque
In the globalization era, the competition faced by all business organizations cannot be bypassed by Small and Medium Enterprises (SMEs) in Bangladesh. Consequently, it seems that numerous Bangladeshi SMEs have closed down within a few years of starting their operational activities, due to lack of proper marketing strategy and appropriate entrepreneurial behavior. In the world of stiff competition among entrepreneurs, entrepreneurial marketing enhances the performance of SMEs. Hence, Bangladeshi SMEs need to be oriented with the entrepreneurial marketing approach to improve their firm performance and to cope with the ever-changing complex global business environment. The main aim of this study is to analyze the effects of entrepreneurial marketing on the performance of Bangladeshi SMEs. A model is drawn based on the past literature to evaluate the relationship between entrepreneurial marketing and SME performance, mediated by competitive advantage. A total of 310 owners of SMEs in Bangladesh were randomly selected as respondents and data have been collected through the questionnaire survey. The data was analyzed by using Statistical Package for the Social Sciences-Analysis of Moments Structures (SPSS-AMOS) software version 21.0. The results showed that there was a significant direct effect of entrepreneurial marketing on the performance of SMEs in Bangladesh. Entrepreneurial marketing also had a significant relationship with competitive advantage. However, competitive advantage did not playa mediator role in the relationship of entrepreneurial marketing and firm performance in this particular study. This research characterizes relevant capabilities of entrepreneurial marketing and highlights the contribution of entrepreneurial marketing on SMEs performance in Bangladesh. At the corporate level, the study generates outlines the SMEs advancement of their marketing related decisions. Finally, this study showed that entrepreneurial marketing is important for the performance and growth of Bangladeshi SMEs. By adopting this strategy, SMEs could become more competitive, flexible and hence having a better performance.